An amine-bifunctionalization strategy with Beta/KIT-6 composite as a support for CO2 adsorbent preparation. Issue 56 (15th September 2020) - Yuan, Yuan; Wei, Jianwen; Geng, Linlin; Mei, Dejun; Liao, Lei
Abstract : CO2 adsorption curves of A-BK-TEPA-50 at 40, 60, 75, 80 and 90 °C. Abstract : An amine-bifunctionalized composite strategy was used to fabricate grafted-impregnated micro-/mesoporous composites for carbon dioxide capture. The micro-/mesoporous Beta/KIT-6 (BK) composite containing a high-silica zeolite with a three-dimensional twelve-membered ring crossing channel system and cubic structural silica was used as a support, and 3-aminopropyltrimethoxysilane (APTS) and tetraethylenepentamine (TEPA) were used as the grafted and impregnated components, respectively. The amine efficiency, adsorption kinetics, thermal stability, regeneration performance, and the effects of impregnated amine loadings (30–60%) and temperatures (40–90 °C) on the CO2 adsorption performance were investigated using a thermal gravimetric analyzer (TGA) in the mixed gases (15 vol% CO2 and 85 vol% N2 ). At 60 °C, the bifunctionalized Beta/KIT-6 (1 mL APTS g −1 BK) displayed the highest CO2 adsorption capacity of 5.12 mmol g −1 at a TEPA loading of 50%. The kinetic model fitting results showed that the CO2 adsorption process was a combination of physical and chemical adsorption, wherein the chemical adsorption is dominant. After five adsorption/desorption cycle regenerations, the saturated adsorption capacity of the composite material was 4.86 mmol g −1, which was only 5.1% lower than the original adsorption capacity. The composites demonstrated excellent CO2 adsorption performance, indicating the promising future of these adsorbents for CO2 capture from actual flue gas after desulfurization.